The Effect of Profitability, Leverage and Company Size on Company Value with Managerial Ownership as a Moderating Variable in the Transportation and Logistics Sector on the Indonesia Stock Exchange in the 2019-2024 Period - Laksono Sulistyobudi, Y Tri; Buchory, Herry Achmad (Dinasti Publisher, 2026)
This research aims to investigate the influence of profitability, leverage, and firm size on firm value, as well as to assess the moderating role of managerial ownership in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX). The inclusion of managerial ownership as a moderating variable is important to evaluate whether insider shareholding can mitigate agency conflicts and influence how these financial factors ultimately affect firm value. The study employs panel data regression using the Moderated Regression Analysis (MRA) approach, with E-Views software utilized for data processing. The population consists of transportation and logistics firms listed on the IDX that published financial statements from 2019 to 2024, and samples were selected using purposive sampling based on data completeness. The findings indicate that profitability and firm size have a positive and significant effect on firm value, while leverage has a negative and significant effect. Collectively, the three independent variables significantly influence firm value. Additionally, the study finds that managerial ownership moderates the relationship between leverage and firm value but does not moderate the effects of profitability or firm size on firm value.